Does the waggle dance help honey bees to forage at greater distances than expected for their body size? - Ratnieks, Francis L. W.; Shackleton, Kyle (Frontiers in Ecology and Evolution, 2015)
A honey bee colony has been likened to an oil company. Some members of the company or colony prospect for valuable liquid resources. When these are discovered other group members can be recruited to exploit the resource. The recruitment of nestmates to a specific location where there is a patch of flowers should change the economics of scouting, that is, the search for new resource patches. In particular, communication is predicted to make scouting at longer distances worthwhile because a profitable resource patch, once discovered, will enhance the foraging not only of the discoverer but also of nestmates that can be directed to the patch. By virtue of having large colonies and dance communication, honey bees are predicted to be able to profitably scout, and hence forage, at greater distances from the nest than either solitary bees or social bees without communication. We test this hypothesis by first examining existing data on foraging distance to evaluate whether honey bees do indeed forage at greater distances than other bees given their body size. Second, we present a simple cost-benefit analysis of scouting which indicates that communication causes longer range scouting to be more profitable. Overall, our analyses are supportive, but not conclusive, that honey bees forage further than would be expected given their size and that the waggle dance is a cause of the honey bee’s exceptional foraging range.